2017
DOI: 10.1016/j.marpetgeo.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Basin scale distribution of organic matter in marine fine-grained sedimentary rocks: Insight from sequence stratigraphy and multi-proxies analysis in the Montney and Doig Formations

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…However, internal sequence stratigraphic frameworks vary greatly between workers (Figure ). The majority of studies have focused on the proximal parts of the formation (Davies et al , ; Markhasin, ; Moslow and Davies, ; Kendall, ; Moslow, ; Panek, ), isolated to localized spatial areas (Evoy and Moslow, ; Evoy, ; Harris, ; Dixon, ; ; ; ; Golding et al , ; Moslow et al , ; Proverbs et al , ; Zonneveld and Moslow, ) or isolated stratigraphic intervals (Euzen et al , ; Prenoslo et al , ), with only a few studies looking at sequence stratigraphic correlations on a larger, basin‐wide scale (Crombez et al , ; ; Davies and Humes, ; Davies et al , ). Although the scope of each publication differs, no unanimous sequence stratigraphic framework has emerged for the Lower and Middle Triassic, and the sequence stratigraphic surfaces identified are varied (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, internal sequence stratigraphic frameworks vary greatly between workers (Figure ). The majority of studies have focused on the proximal parts of the formation (Davies et al , ; Markhasin, ; Moslow and Davies, ; Kendall, ; Moslow, ; Panek, ), isolated to localized spatial areas (Evoy and Moslow, ; Evoy, ; Harris, ; Dixon, ; ; ; ; Golding et al , ; Moslow et al , ; Proverbs et al , ; Zonneveld and Moslow, ) or isolated stratigraphic intervals (Euzen et al , ; Prenoslo et al , ), with only a few studies looking at sequence stratigraphic correlations on a larger, basin‐wide scale (Crombez et al , ; ; Davies and Humes, ; Davies et al , ). Although the scope of each publication differs, no unanimous sequence stratigraphic framework has emerged for the Lower and Middle Triassic, and the sequence stratigraphic surfaces identified are varied (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the sedimentology, stratigraphy and sequence stratigraphy of the Montney and Doig formations (Davies et al , ; Embry, ; Golding et al , ; Crombez et al , ; ; Davies et al , ; Proverbs et al , ). The Sunset Prairie Formation, however, was not recognized by these studies, and the interval was either included in the Montney or Doig formations (Doig phosphate zone), or straddled both.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of the sedimentology highlighted an interval of turbiditic deposits and an interval of phosphatic shale deposits (Golding et al, 2014). Recent work showed that the studied interval was deposited in a marine basin with a maximum estimated bathymetry of 300 m (Crombez, 2016;Crombez et al, 2016b). Study on the organic content shows that these formations can be considered as a type II/III marine source rock with actual hydrogen index up to 600 mgHC/gTOC and TOC up to 12 wt% (Riediger, 1997;Riediger et al, 1990).…”
Section: The Montney and Doig Formationsmentioning
confidence: 96%
“…Recent studies on the stratigraphic architecture of these formations (Crombez, 2016;Crombez et al, 2016b) show that the Montney and Doig/Halfway Formations respectively represent the expression of two second order stratigraphic cycles (sequence A and B). Moreover, the Montney Formation (sequence A) is subdivided in three third order sequences (sequence 1, 2 and 3) that respectively represent the second order TST (transgressive systems tract), HST (highstand systems tract) and FSST (falling stage systems tract); whereas the Doig and Halfway Formations (sequence B) were only subdivided into 2 system tracts: the transgressive system tract 4 (TST4) and the highstand system tract 4 (HST4, Fig.…”
Section: The Montney and Doig Formationsmentioning
confidence: 99%
See 1 more Smart Citation